Characterization of a new radiochromic three-dimensional dosimeter - Guo, P. Y. (2006)
The development of intensity-modulated radiotherapy (IMRT) has created a clear need for a dosimeter that can accurately and conveniently measure dose distributions in three dimensions to assure treatment quality. PRESAGE™ is a new three dimensional (3D) dosimetry material consisting of an optically clear polyurethane matrix, containing a leuco dye that exhibits a radiochromic response when exposed to ionizing radiation. A number of potential advantages accrue over other gel dosimeters, including insensitivity to oxygen, radiation induced light absorption contrast rather than scattering contrast, and a solid texture amenable to machining to a variety of shapes and sizes without the requirement of an external container. In this paper, we introduce an efficient method to investigate the basic properties of a 3D dosimetry material that exhibits an optical dose response. The method is applied here to study the key aspects of the optical dose response of PRESAGE™: linearity, dose rate dependency, reproducibility, stability, spectral changes in absorption, and temperature effects. PRESAGE™ was prepared in 1×1×4.5 cm(3) optical cuvettes for convenience and was irradiated by both photon and electron beams to different doses, dose rates, and energies. Longer PRESAGE™ columns (2 ×2×13 cm(3)) were formed without an external container, for measurements of photon and high energy electron depth-dose curves. A linear optical scanning technique was used to detect the depth distribution of radiation induced optical density (OD) change along the PRESAGE™ columns and cuvettes. Measured depth-OD curves were compared with percent depth dose (PDD). Results indicate that PRESAGE™ has a linear optical response to radiation dose (with a root mean square error of ∼1%), little dependency on dose rate (∼2%), high intrabatch reproducibility (<2%), and can be stable (∼2%) during 2 hours to 2 days post irradiation. Accurate PRESAGE™ dosimetry requires temperature control within 1 °C. Variations in the PRESAGE™ formulation yield corresponding variations in sensitivity, stability, and density. CT numbers in the range 100–470 were observed. In conclusion, the small volume studies presented here indicate PRESAGE™ to be a promising, versatile, and practical new dosimetry material with applicability for radiation therapy.